Propriedades citotóxicas e mecanismo de ação de novos complexos fosfínicos de rutênio(II) contendo ligantes naftoquinonas - Costa, Analu Rocha (Universidade Federal de São Carlos, 2022)
In this study, two series of ruthenium(II)-phosphine complexes containing naphthoquinone ligands were synthesized, characterized, and investigated regarding the cytotoxic activity. The first series represents the compounds (A1-A8), with the general formula: [Ru(NQ1)(bipy)(PPh3)2]PF6 (A1); [Ru(NQ1)(bipy)(P-P)]PF6 (A2-A7) and [Ru(NQ1)(dppm)2]PF6 (A8), where (NQ1 = 3-styryl-lauosne; P-P = bis-(diphenylphosphine) )methane (dppm), 1,2-bis(diphenylphosphine)ethane (dppe), 1,3-bis(diphenylphosphine)propane (dppp), 1,4-bis(diphenylphosphine)butane (dppb), 1,2-bis (diphenylphosphine)ethylene (dppen) and bis[(2-diphenylphosphine)phenyl)ether] (DPEphos). The second series consisted of four compounds (B1-B4) with the general formula [Ru(NQn)(bipy(P-P)]PF6, where (NQn = lawsone or lapachol; P-P = cis-1,2-bis(diphenylphosphine)ethylene (dppen) and bis-[(1-diphenylphosphine)phenyl]ether (DPEphos).The compounds were characterized by elemental analysis, infrared spectroscopy, nuclear magnetic resonance (1H NMR, 13C{1H} and 31P{1H}), conductivity molar, cyclic voltammetry, mass spectrometry and X-ray diffraction (single crystal).Compound/DNA interaction studies, using viscosity measurements, gel electrophoresis. The competition assay with Hoechst 33258, demonstrated that the ruthenium complexes of series 1 and 2 interact via the DNA minor groove. Complex/HSA interaction studies have shown that the complexes have the ability to interact with the biomolecule, with binding constants (Kb) of the order of 103 to 105, indicating weak to moderate interactions and affinity for HSA site I. The cytotoxic screening of the complexes was real It was performed on MDA-MB-231, MCF-7, SK-BR-3 and A549 lung tumor cell lines and on non-tumor breast (MCF-10A) and lung (MRC-5) cell lines. All compounds were cytotoxic in the strains tested, exhibiting lower IC50 values than the free ligands and the reference drug cisplatin. The complexes (A1 and A6) from series 1 and (B2 and B4), from series 2, were the most active and selective against MDA-MB-231 breast tumor cells. The in vitro assays with the MDA-MB-231 strain, demonstrated that the compounds A1 and A6 altered the cellular morphology and inhibited the cell migration process from the Wound Healing assay. The cell cycle distribution profile for the A1 complex indicates an accumulation of cells in the Sub-G0 phase and DNA fragmentation that is indicative of cell death by apoptosis. However, there were no significant changes in the other phases of the cell cycle. The results of the apoptosis assay performed by flow cytometry showed that the complexes induce death by apoptosis in a concentration-dependent manner. In view of this study the twelve ruthenium(II) complexes have great potential as antitumor metallopharmaceuticals.
Cytotoxic properties and mechanism of action of new ruthenium(II) phosphine complexes containing naphthoquinone ligands
Keywords: Complexos de rutênio; Naftoquinonas; Anticâncer; Ruthenium complex; Lawsone; Lapachol; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA